Fine Needle Aspiration Cytology (FNAC) for Chinese Patients With Acral and Cutaneous Melanoma: Accuracy and Safety Analysis From a Single Institution - Yang, Lingge; Sun, Wei; Xu, Yu; Zhang, Xun; Wang, Shengping; Wang, Chunmeng; Chen, Yong (Frontiers in Oncology, 2020)
Biopsy with full histopathological information for melanoma is strongly recommended in the era of target and immunotherapy. Fine needle aspiration cytology (FNAC) for primary and regional lymph nodes has been implied in making a decision of resection and repair. The purpose of this study was to investigate the accuracy and safety of FNAC in Chinese patients with acral and cutaneous melanoma, and to evaluate the influencing factors and its impact on prognosis. Data of 128 patients with stage 0-III acral and cutaneous melanoma who were treated in Fudan University Shanghai Cancer Center from 2009 to 2016 were retrospetively collected from a prospective database. All these Patients had FNAC on primary lesions or superficial lymphatic lesions. In addition, we matched 128 patients who did not have FNAC from the database with similar parameters as matched group. Clinical features, FNAC status and recurrence or metastasis status of all 258 patients were analyzed for overall survival (OS), melanoma-specific survival (MSS), recurrence-free survival (RFS) and metastasis-free survival (MFS). Of the 128 cases with FNAC, 5.5% cases (7/128) had negtive cytology diagnosis, 12.2% (5/41) in primary lesion and 2.3% (2/87) in lymph nodes. Tumor thickness ,status of ulceration and subtype were not associated with accuracy for both primary and lymph nodes FNAC. With a median follow-up of 40 (1-144) months in all 256 patients, there were 55 cases of melanoma-specific death and the median OS was 95 months, median MSS was 104 months. In comparison with matched group, patients with FNAC had significant worse OS (P = 0.0242). Tumor progression occurred in 130 patients. Survival analysis revealed differences in OS (P = 0.0379) and DFS (P = 0.0012) between the two groups. The effect of FNAC was on patients' RFS (P = 0.0009) and MFS (P = 0.0136), while the difference in survival curves of RFS (P = 0.0013) and MFS (P = 0.0043) was also statistically significant. For Chinese patients with acral and cutaneous melanoma, FNAC on primary or superficial lymphatic lesions was a good tool for disease diagnosis, but it was associated with adverse impact on prognosis.